Evaporation heat transfer and pressure drop of the interim (R-448A, R-449A) and long term (R-455A, R-454C) low GWP R-404A alternative refrigerants in a smooth tube. (December 2021) - Kim, Cheol-Hwan; Kim, Nae-Hyun
Highlights: Four R-404A alternative refrigerants (R-448A, R-449A, R-455A, R-454C) are tested under evaporation condition. Alternate refrigerants yield higher heat transfer coefficients at a low mass flux. The trend is reversed at a high mass flux and high vapour quality. Pressure drops of the alternative refrigerants are larger than those of R-404A. Gungor and Winterton [8] correlation reasonably predicts the heat transfer coefficients. Abstract: Due to the global warming issue, R-404A phases out, and new alternative refrigerants are emerging. In this study, four R-404A alternative refrigerants - two interim refrigerants (R-448A, R-449A) and two long term refrigerants (R-455A, R-454C) - including R-404A were tested in a 5.6 mm inner diameter tube under evaporation condition. The test range included the mass flux from 90 to 300 kg/m 2 s, heat flux from 5 to 15 kW/m 2, and vapor quality from 0.2 to 0.8. The saturation temperature was 10 °C. The results showed that, at a low mass flux, the heat transfer coefficients of R-404A were higher than those of the alternative refrigerants. At a high mass flux and high quality, on the other hand, the reverse was true - the heat transfer coefficients of R-404A were lower than those of the alternative refrigerants. The pressure drops of the alternative refrigerants were larger than those of R-404A. Finally, the data are compared with the predictions by existing correlations.